Building a maritime community with a shared future: Scholarly reflections on China's new ocean vision. (March 2023) - Xu, Qi; Tan, Ziyue
Abstract: The initiative of Building a Maritime Community with a Shared Future (MCSF) has gained widespread attention domestically since it was proposed by President Xi Jinping in 2019. This article selects and reviews 269 academic articles published from 2019 to 2022 and classifies them according to their subjects. The paper, in four parts, makes reflections on building the MCSF from Chinese Academia. The introductory section describes the background of the MCSF. The second part explores a theoretical outlook of the literature on building the MCSF. Chinese scholars have examined the definition and specific contents of the MCSF. In addition, scholars further delve into the theoretical roadmaps of the MCSF including its theoretical foundation and promotion of international ocean governance theory. The third part analyses how to adopt a series of pragmatic approaches to build the MCSF in diverse ocean-related fields from both international and domestic perspectives. The fourth part gives concluding remarks.